2022
DOI: 10.3390/nu14102019
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Time-of-Day of Energy Intake in a Chinese Cohort

Abstract: Few studies have described the status and change of time-of-day of energy intake on a population level. This study aims to investigate the secular trend in time-of-day of energy intake using a Chinese cohort, and to examine demographic disparities in trends. A total of 20,976 adults with at least two waves of dietary data in the China Health and Nutrition Survey (CHNS 1991–2018) were included. A multilevel linear mixed model was applied to the energy proportions of breakfast, lunch and dinner. A multilevel Tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For instance, data indicate a rise in meal frequency from three to five times a day and an increase in the percentage of energy from snacks between 1971 and 2010 among US adults [ 14 ]. In the Chinese population, upward trends in the percentage of energy from snacks were observed between 1991 and 2018 [ 18 ]. A prospective cohort study has demonstrated a positive association between self-reported between-meal snacking and a risk of substantial weight gain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, data indicate a rise in meal frequency from three to five times a day and an increase in the percentage of energy from snacks between 1971 and 2010 among US adults [ 14 ]. In the Chinese population, upward trends in the percentage of energy from snacks were observed between 1991 and 2018 [ 18 ]. A prospective cohort study has demonstrated a positive association between self-reported between-meal snacking and a risk of substantial weight gain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%